2005
DOI: 10.1128/jvi.79.18.12081-12087.2005
|View full text |Cite
|
Sign up to set email alerts
|

The 41-Amino-Acid C-Terminal Region of the Hepatitis E Virus ORF3 Protein Interacts with Bikunin, a Kunitz-Type Serine Protease Inhibitor

Abstract: Hepatitis E virus (HEV), a human plus-stranded RNA virus, contains three open reading frames (ORF).Of these, ORF1 encodes the viral nonstructural polyprotein, ORF2 encodes the major capsid protein, and ORF3 codes for a phosphoprotein of undefined function. Recently, using the yeast two-hybrid system to screen a human cDNA liver library, we have isolated and characterized AMBP (␣ 1 -microglobulin/bikunin precursor), which specifically interacts with the ORF3 protein of HEV. The ORF3 protein expedites the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…The exact functions of vp13 in HEV infection remain unknown although the findings of a number of studies have shown that it plays a role in cellular signaling pathways (13,17,24,(34)(35)(36)40). During subcellular fractionation of COS-7 cells transfected with a vp13-expressing plasmid, vp13 was found to partition with the cytoskeletal fraction (40).…”
Section: Hepatitis E Virus (Hev) Is the Causative Agent Of Hepatitis mentioning
confidence: 99%
“…The exact functions of vp13 in HEV infection remain unknown although the findings of a number of studies have shown that it plays a role in cellular signaling pathways (13,17,24,(34)(35)(36)40). During subcellular fractionation of COS-7 cells transfected with a vp13-expressing plasmid, vp13 was found to partition with the cytoskeletal fraction (40).…”
Section: Hepatitis E Virus (Hev) Is the Causative Agent Of Hepatitis mentioning
confidence: 99%
“…Interestingly, ORF3 is not necessary for in vitro infection (20) but is necessary for in vivo infection of macaques (21). It is most likely multifunctional (19) and involved in pathogenesis (22)(23)(24)(25). Most of the coding region in the HEV genome is under purifying selection (26,27), i.e., selection against change in the amino acid sequence.…”
mentioning
confidence: 99%
“…It has been reported that recombinant ORF3 protein forms dimers through amino acid residues 81 to 123 (28); interacts with ORF2 protein mediated by amino acid residues 57 to 81 (23); binds various SH3 domain-containing proteins via amino acid residues 75 to 113 and activates mitogen-activated protein kinase (12); and interacts with a liver-specific protein, ␣ 1 -microglobulin/bikunin precursor (AMBP), and its two processed proteins, ␣ 1 m (26) and bikunin (27), through the C-terminal region (amino acid residues 81 to 123). These data indicated that the C-terminal region of the HEV ORF3 protein is a multifunctional domain.…”
mentioning
confidence: 99%